Immune response and possible therapeutics in COVID-19. Issue 2 (4th January 2021) - Dutta, Anindya; Roy, Ananya; Roy, Laboni; Chattopadhyay, Samit; Chatterjee, Subhrangsu
Abstract : While the world stands a witness to the havoc of COVID-19, we must continue our quest of exploring various small molecule drugs and biologics as therapeutic strategies to fight the pandemic. Abstract : COVID-19 has emerged as a pandemic affecting about 213 countries in all the continents of the globe, resulting in more than 37.8 million individuals getting infected and over 1.08 million deaths worldwide, jeopardizing global human health and the economy. This presents an urgent need to develop therapies that target the SARS-CoV2 virus specifically. This review aims at presenting the available information on the coronavirus disease 2019 along with various drugs that are having widespread use until a vaccine candidate is available to aid in the development of therapeutic strategies against COVID-19.